2020
DOI: 10.1093/tropej/fmaa041
|View full text |Cite
|
Sign up to set email alerts
|

Pediculosis Affects Mexican Children from Different Socioeconomic Status Equally: A Cross-Sectional Study

Abstract: SUMMARY The prevalence of pediculosis in Mexican children was studied in San Nicolas and Tapachula, Mexico. A cross-sectional study included 888 students between six and 12 years old from two urban communities with an unequal socioeconomic status between September 2015 and March 2016. A Pearson χ2 and multivariate logistic analysis were carried out to associate risk factors to pediculosis. The overall prevalence of pediculosis from both localities was 23.9%. The female gender; long and medium ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…Our present and previous studies revealed a frequent occurrence of pediculosis capitis, as cases of infestation were noted in 87.5% of the surveyed schools. Similar to other studies of this type, the present observations indicate a higher prevalence of head lice in girls, although the relationship between P. humanus infestation and the sex of the children turned out to be statistically insignificant [29,32,33]. In the present study, the highest prevalence of infestation (68.0%) was found in the group of the early-school aged children (6-9 years).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our present and previous studies revealed a frequent occurrence of pediculosis capitis, as cases of infestation were noted in 87.5% of the surveyed schools. Similar to other studies of this type, the present observations indicate a higher prevalence of head lice in girls, although the relationship between P. humanus infestation and the sex of the children turned out to be statistically insignificant [29,32,33]. In the present study, the highest prevalence of infestation (68.0%) was found in the group of the early-school aged children (6-9 years).…”
Section: Discussionsupporting
confidence: 89%
“…Human lice (both genera Pediculus and Pthirus) seem to represent the oldest permanent ectoparasites of Homo sapiens [26,27]. Despite the progress in medical science and development of the civilization, pediculosis capitis is still an important health issue worldwide [1,28,29]. A large variation in the global spread of head lice is observed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that the prevalence of pediculosis among boys was lower compared to girls (7% and 19%, respectively). This may be due in large part to the presence of long hair, a risk factor that has been shown in previous studies (Ortega-Marin et al, 2013;Hatam-Nahavandi et al, 2020;Sánchez-Casas et al, 2021).…”
Section: Discussionmentioning
confidence: 67%
“…In Mexico, pediculosis has been shown that it affects up to 60% of school children, with an average prevalence that goes from 15% to 30% (Hatam‐Nahavandi et al, 2020; Sánchez‐Casas et al, 2021). However, in the present study, the overall prevalence of head lice was slightly lower (12.36%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation